2021
DOI: 10.3920/wmj2020.2648
|View full text |Cite
|
Sign up to set email alerts
|

Phytic acid modulates the morphology, immunological response of cytokines and β-defensins in porcine intestine exposed to deoxynivalenol and fumonisin B1

Abstract: Occurrence of mycotoxins in agricultural products represents a risk for human and animal health. Therefore, there is a requirement of strategies to mitigate their harmful impacts. This study investigated the effects of phytic acid (IP6) on the immunological response of pro-(interleukin (IL)-1β, IL-6, IL-8, IL-10, interferon (IFN)-γ, tumour necrosis factor (TNF)-α) and anti-inflammatory (IL-10) cytokines and β-defensins 1 (pBD-1) and 2 (pBD-2) in porcine jejunal explants exposed to deoxynivalenol (DON) and fumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Moreover, IL-10 is the most potent anti-inflammatory factor, which could decrease the inflammation-mediated organs injury [ 26 , 27 ]. Several evidence suggest that DON downregulated the mRNA levels of anti-inflammatory factor IL-10 in the fish and porcine intestine, which was in line with the results of the laying hens [ 28 , 29 ]. These findings suggested that DON-induced inflammatory injury of the intestine contributed to the release and recruitment of pro-inflammatory mediators and restrain anti-inflammatory factors, which promoted an inflammatory response and induced the intestinal barrier injury.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, IL-10 is the most potent anti-inflammatory factor, which could decrease the inflammation-mediated organs injury [ 26 , 27 ]. Several evidence suggest that DON downregulated the mRNA levels of anti-inflammatory factor IL-10 in the fish and porcine intestine, which was in line with the results of the laying hens [ 28 , 29 ]. These findings suggested that DON-induced inflammatory injury of the intestine contributed to the release and recruitment of pro-inflammatory mediators and restrain anti-inflammatory factors, which promoted an inflammatory response and induced the intestinal barrier injury.…”
Section: Discussionsupporting
confidence: 81%
“…Current results show that PA cotreatment retains the axonal length and increases the survivability of CDDP-treated cells significantly ( P < 0.001). PA has been reported to have many beneficial effects in neuroprotection in Alzheimer’s disease, homeostasis, anticancer properties and inflammation control . Absorption of excessive iron, a significant factor in causing Alzheimer’s disease, was the reason behind neuroprotection .…”
Section: Discussionmentioning
confidence: 99%